Faculdade Senai na perspectiva da educação profissional inclusiva do estudante esclerose multipla - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
This research presents as its theme: pedagogical practices developed with students who have intellectual disabilities and multiple sclerosis at Faculdade SENAI/Anápolis. The study highlights inclusive education, professional education from the perspective of inclusive education and the possibilities of learning based on Vygotsky's concept of compensation. The guiding question of the study was: how and what have been the inclusive pedagogical practices used in SENAI professional education to consolidate the learning of students with multiple sclerosis? The general objective was: to investigate the use of inclusive pedagogical practices in SENAI professional education to consolidate the learning of students with multiple sclerosis. As for the specific objectives, they were: a) identify the conceptions of teachers at Faculdade Senai regarding the inclusion of students with multiple sclerosis in Professional Education; b) check with teachers which inclusive pedagogical practices are developed to consolidate the learning of students with ID; c) develop and apply a didactic sequence containing flexible pedagogical practices to facilitate the learning of students with Multiple Sclerosis in Professional Education; and, d) verify the contributions of applying the didactic sequence to the process of cognitive, professional and socio-emotional development of students with Multiple Sclerosis. From a methodological point of view, this research uses a qualitative approach. And, as a data collection instrument, in addition to the literature review, observations, semi-structured interviews and reports were carried out. The environment chosen for the research was SENAI College - Anápolis. To this end, the class's mechanical automation classes were observed at night. The research subjects were professionals who work as support teachers for students with intellectual disabilities. Finally, an educational product was created: a pedagogical ebbok on Special Education. The text was structured into three chapters. In the first, a reflection on professional education in Brazil and the creation of SENAI is presented; the path of public education policies for special and inclusive education; and, how SENAI organizes itself to meet this education perspective. In chapter two, considerations are presented on Vygotsky's theory of compensation. In this sense, it is clear how this author's studies can contribute to the promotion of pedagogical practices that contribute to special and inclusive education. And, in chapter three, still under construction, the empirical research is presented. The research showed a methodological and pedagogical alternative based on Vygotsky's understanding of defectology; In this way, it proposes the use of special technical and methodological resources that allow people to compensate for their limitations by creating other ways that guarantee their insertion into productive life in full collaboration with non-disabled people. Thus consistent with dialectical thinking, the author emphasizes in deficiency the tendency towards its opposite, potency.
Senai Faculty from the perspective of inclusive professional education for multiple Sclerosis students
Keywords: Educação Inclusiva; Esclerose múltipla; Serviço Nacional de Aprendizagem Industrial (SENAI); Praticas pedagógicas; Inclusive Education; Multiple; SENAI; Pedagogical pratices; CIENCIAS HUMANAS::EDUCACAO; TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL